Analysis of Animal Structure Practicum Module based Virtual Lab - Maspupah, Meti; Hidayah, Nurul (Universitas Muhammadiyah Surakarta, 2024)
Practicum as part of the biology learning process plays an important role in developing students' mastery of material concepts. Limitations on the conditions for the practicum implementation, making the practicum module as a guide for activities experiencing more advanced development. The purpose of this study was to find out how students responded to the virtual lab-based practicum module in animal structure courses. The device used is a student response questionnaire consisting of seven aspects related to the virtual lab-based practicum module. The results suggest that 53.7% of student responses agree, and 37% strongly agree with the attachment and use of the virtual lab in practicum. Additional components such as interactive modules that get responses of 55.6% agree and 42.6% strongly agree are further considerations in understanding student responses to practicum activities. The use of a virtual lab as a new development of the animal structure practicum module is considered capable of developing and increasing students' understanding.